Hepatogenous diabetes. Current views of an ancient problem - García Compeán, Diego; Jáquez Quintana, Joel Omar; Maldonado Garza, Héctor Jesús (Elsevier España, 2009)
Diabetes developed as a complication of cirrhosis is known as «hepatogenous diabetes» (HD). Around 30% to 60% of cirrhotic patients suffer from this metabolic disorder. Insulin resistance in muscular, hepatic and adipose tissues as well as hyperinsulinemia, seem to be pathophysiologic bases for HD. An impaired response of the islet E-cells of the pancreas and the hepatic insulin resistance are also contributing factors. Diabetes develops when defective oxidative and nonoxidative muscle glucose metabolism develops. Non-alcoholic fatty liver disease (NAFLD), alcoholic cirrhosis, chronic hepatitis C (CHC), and hemochromatosis are more frequently associated with HD. HD in early cirrhosis stages may be subclinical. Only insulin resistance and glucose intolerance may be observed. As liver disease advances, diabetes becomes clinically manifest, therefore HD may be considered as a marker for liver function deterioration. HD is clinically different from that of type 2 DM since it is less frequently associated with microangiopathy and patients suffer complications of cirrhosis more frequently as well as increased mortality. Insulin resistance and HD associate to a decrease in the sustained response to antiviral therapy and an increased progression of fibrosis in patients with CHC. Diabetes treatment is complex due to liver damage and hepatotoxicity of oral hypoglycemic drugs that are frequently prescribed to these patients. This paper will review current concepts in relation to the pathophysiology, the impact on the clinical outcome of cirrhosis, and the therapy of HD. Finally, the role of HD as a risk factor for the occurrence and exacerbation of hepatocellular carcinoma (HCC) will also be reviewed.